PERAN PENDIDIKAN ISLAM DALAM MENGHADAPI KRISIS MORAL DAN KARAKTER MAHASISWA DI ERA GLOBALISASI - Farida Amalliya Oktaviani; Khanna Dewi Yukhanid; Khoirotul Muntaha Binti Salis; Qoirun Nafiah; Salma Nurya Mumtaza (Prodi PAI Fakultas Tarbiyah IAI Sunan Giri Trenggalek, 2025)
This journal is compiled to investigate the role of Islamic education in addressing the moral and character crisis among university students in the era of globalization. A qualitative research method is employed, specifically utilizing a literature review approach. This involves gathering data through an examination of books, literature, notes, and reports related to the discussed issue. Islamic education plays a crucial role in shaping individual character by instilling noble moral values and ethics. Beyond enhancing intellectual intelligence, it aims to cultivate individuals who are faithful, pious, and in accordance with Islamic teachings. This education is carried out through activities in families, educational institutions, and the community, involving parents, social activities, and expressions of Islamic culture. The utilization of technology also supports Islamic education by disseminating religious values through social media, enabling the younger generation to learn anytime and anywhere. Technology helps create engaging and relevant learning experiences in line with the times.